Southern Highbush Blueberry Cultivars from the University of Florida - Doug Phillips; Jeffrey Williamson; Paul Lyrene; Patricio Munoz (EDIS, 2024)
Cultivar selection involves weighing the advantages and disadvantages of a cultivar relative to the grower’s needs. Unfortunately, there are no perfect cultivars suited for every location and management system. The following discussion categorizes southern highbush cultivars into three groups: (1) new cultivars; (2) established cultivars; and (3) secondary and obsolete cultivars.